Perkembangan Konsumsi dan Proyeksi Permintaan Beras di Indonesia - nFN Erwidodo; Mewa Ariani; Adreng Purwoto (Jurnal Agro Ekonomi, 1997)
This paper describes some analysis results of Susenas data on rice consumption in Indonesia during 1990-1993 and its projection in the future. The results show that participating rate of rice consumption in some provinces is increasing . Based on the participating rate, demand for local rice tended to increase during the period of 1990-1993. However, in rice-producing provinces demand for rice of improved varieties were greater than that for local rice. For the period of 1990-1993 per capita rice consumption decreased in most of the provinces, except in provinces where rice consumption was low, such as provinces of Central Java, Yogyakarta, East Java, East Nusa Tenggara, North Sulawesi, South-east Sulawesi and Irian Jaya. Demand function analysis showes that income elasticity of rice was still positive but its elasticity values tend to decline. On the other hand, income elasticities on per capita rice consumption in regions of low per capita rice consumption were greater relatively than those in region of high per capita rice consumption. Projection of rice consumption and production for the period of 1993-2003 show that domestic rice production (in the normal climate) was still higher than rice consumption demand. It meant that rice self-sufficiency could be maintained. Increase of rice import volume, especially in 1995 which was more than 2 million tons was more affected by domestic rice production decline due to drought. Furthemore, rice import policy is an important part of national rice "stock" management to stabilise rice price, including to fulfill rice package for civil servants/military.